2007
DOI: 10.2341/06-36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on the Fluoride Release and Recharging Ability of Glass Ionomers

Abstract: SUMMARYThis study investigated the effects of environmental temperature on the fluoride release and recharging ability of glass ionomers. Five disk specimens (15 mm in diameter and 1 mm thick) were made of each of the following materials: a conventional luting glass ionomer, two high viscosity restorative glass ionomers and a restorative resin-modified glass ionomer. The fluoride release of each material was measured at 4°C, 37°C and 55°C. An additional three groups, which were made of the same materials, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 14 publications
(12 reference statements)
6
19
0
Order By: Relevance
“…The pattern of recharge for the conventional glass ionomers after a sharp rise followed by a rapid decline and then gradual prolonged release which are similar to those reported in other studies[2124] except for the data reported by Rao et al ., indicating no significant rechargability for Fuji VII for up to 30 days after exposure to a 1000 ppm fluorinated dentifrice. [25] All the tested materials reacted positively to exposure to external fluoride source.…”
Section: Discussionsupporting
confidence: 89%
“…The pattern of recharge for the conventional glass ionomers after a sharp rise followed by a rapid decline and then gradual prolonged release which are similar to those reported in other studies[2124] except for the data reported by Rao et al ., indicating no significant rechargability for Fuji VII for up to 30 days after exposure to a 1000 ppm fluorinated dentifrice. [25] All the tested materials reacted positively to exposure to external fluoride source.…”
Section: Discussionsupporting
confidence: 89%
“…7 However, sensitivity to moisture contamination interferes with the initial setting of self-cured GIC. In addition, conventional GICs are relatively unaesthetic and have poorer mechanical properties than resin composites, 8 which might impair the long-term treatment of DH. In fact, resin-modified glass ionomer cements have been developed to overcome the disadvantages of conventional GIC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the effects of several desensitizing agents were not permanent because they did not properly adhere to the dentin surface. 6,8,13 However, a limited amount of data on the efficacy of desensitizers is available in the literature, especially for long-term assessments of at least 6-months follow-up. 2,4,18,19 Therefore, current randomized, split-mouth clinical trial evaluates and compares the desensitizing efficacy of Clinpro XT and conventional GIC (Vidrion R) in a 6-month follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the release of fluoride ions from glass ionomer cements continued for longer than a year [25]. Furthermore, the fluoride-releasing ability of glass ionomer cements may be regenerated or recharged by the use of solutions of high fluoride concentration, such as mouth rinses and topical applications [26][27][28][29], and the discoloration effect thus may last a long time.…”
Section: Discussionmentioning
confidence: 99%